Financial Distress Analysis Using Altman Z-Score Model In Sharia Banking In Indonesia - Firman Setiawan (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
This study is conducted to explain the risk of financial failure that may occur in Sharia banking which is known asfinancial distress. Quantitative data in the formof financial ratios fromseveral Islamic banks which are the object of the study were analyzed using Altman Z- score model. After analyzing it, it is known that at Bank BRI Syariah Inc, the company experienced financial distress in 2015, in the following year the company experienced improvementthus in 2016-2019, the company was in good health. Bank BTPN Syariah Inc in 2015-2019 was in a good condition, which means that there was no financial distress or was in a gray area position. Bank Syariah Mandiri Inc experienced financial distress in 2015-2019, which means that during that time the company was in a gray area position